2009
DOI: 10.1144/1354-079309-793
|View full text |Cite
|
Sign up to set email alerts
|

Flow processes and pressure evolution in aquifers during the injection of supercritical CO 2 as a greenhouse gas mitigation measure

Abstract: ABSTRACT:Regional saline aquifers offer the greatest potential for very large-scale underground CO 2 storage as a means of mitigating greenhouse gas emissions. Their dynamic storage capacity, in terms of induced increases in formation pressure, will limit the rate at which CO 2 can be injected and may ultimately limit the amount of CO 2 that can be stored. Generic flow models have been generated to examine the effects on pressure evolution of various reservoir parameters (dimensions, permeability, porosity, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 32 publications
4
23
1
Order By: Relevance
“…This 547 finding is similar to the results of Chadwick et al (2009a) who showed that near-field pressure 548 (within a 2.5 m radius of the injection well) is inversely proportional to permeability. Increasing 549 storage formation porosity independently of permeability leads to slightly higher pressure at the top 550 of the model (s01a, s01a5).…”
Section: Pressure Buildup and Plume Diameter 531supporting
confidence: 80%
“…This 547 finding is similar to the results of Chadwick et al (2009a) who showed that near-field pressure 548 (within a 2.5 m radius of the injection well) is inversely proportional to permeability. Increasing 549 storage formation porosity independently of permeability leads to slightly higher pressure at the top 550 of the model (s01a, s01a5).…”
Section: Pressure Buildup and Plume Diameter 531supporting
confidence: 80%
“…In fact, development and migration of the CO 2 plume at Sleipner is very much as predicted, with no migration from the storage reservoir so far detected and no leakage. Simulated pressure increase is negligible and this is supported by the measurements (Chadwick et al 2009). For the record, Sleipner has now injected 12 million tonnes of CO 2 at a rate of about 1 million tonnes per year.…”
Section: Pressure Managementsupporting
confidence: 71%
“…In any case it naturally decreases during the injection period as the relative permeability to CO 2 increases (Chadwick et al, 2009). At the end of the injection period there is a rapid pressure fall-off near the injection point as the pressure equilibrates within the model as a whole and a longer term decline due to water leaving the system via the seabed outcrop and the low permeability caprock.…”
Section: The Base Case Simulationmentioning
confidence: 99%